1968
DOI: 10.4141/cjas68-044
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production in Range Beef Cows and Its Relationship to Calf Gains

Abstract: Milk yield in lactating range. beef co\Ms, was estim-ated by Snilkin-g-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0
5

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 5 publications
5
30
0
5
Order By: Relevance
“…The relationship between milk and weaning weight, a function of daily gain, was discussed by Gleddie and Berg (1968), Jeffrey et al (1971) and Butson et al (1980).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between milk and weaning weight, a function of daily gain, was discussed by Gleddie and Berg (1968), Jeffrey et al (1971) and Butson et al (1980).…”
Section: Methodsmentioning
confidence: 99%
“…Melton et al (1967) showed that milk production was 53 kg greater for cows suckling bull calves than for those suckling heifer calves. Rutledge et al (1971) Gleddie and Berg (1968) and Keller (1980) stated that percentages of fat, protein, and SNF were uncorrelated with calf gain in their experiments. However, the amount of each constituent available to the calf influences energy intake and therefore calf gain, regardless of the relative constituent percentages or milk yields.…”
Section: Experimental Herdmentioning
confidence: 99%
“…These increases were associated with decreases in milk volume over the lactation period (Table I). Gleddie and Berg (1968) reported means for VoF, %oP, and …”
mentioning
confidence: 99%